Analisis Ancaman Keberadaan WNI Eks-Foreign Terrorist Fighters ISIS dalam Perspektif Keamanan Nasional - Angga Bimantara; Aji Setyo Wibowo (Universitas Tribhuwana Tunggadewi, 2026)
This study examines the threat analysis of Indonesian ex-foreign terrorist fighters (ex-FTF) affiliated with ISIS from the perspective of national security. The return of these individuals poses complex risks that are not only limited to terrorism, but also extend to ideological radicalization, public security disruptions, international diplomatic pressures, and socio-legal challenges within Indonesia. This research applies a qualitative descriptive method, relying on secondary data from journals, books, and government reports, to identify the multidimensional nature of the issue. The findings indicate that the planned repatriation Indonesian citizens from Camp Al-Hol and Al-Roj requires comprehensive and forward-looking strategies. The study emphasizes the importance of foresight and scenario planning as tools to anticipate potential security developments, combined with intelligence analysis to map vulnerabilities and mitigation measures. Furthermore, effective coordination between national security institutions, community-based deradicalization programs, and international cooperation is crucial in addressing the risks of reintegration. The results highlight that national security must be maintained through adaptive policies that balance security imperatives with humanitarian considerations. Strengthening interagency synergy and preparing multi-scenario strategies are essential to reduce threats and ensure that returnees can be reintegrated into society without generating new security problems.Penelitian ini mengkaji analisis ancaman terhadap keberadaan WNI eks-foreign terrorist fighters (eks-FTF) yang terafiliasi dengan ISIS dalam perspektif keamanan nasional. Kepulangan mereka menimbulkan risiko yang kompleks, tidak hanya sebatas ancaman terorisme, tetapi juga mencakup radikalisasi ideologi, gangguan keamanan publik, tekanan diplomatik internasional, serta tantangan sosial dan hukum di Indonesia. Penelitian ini menggunakan metode deskriptif kualitatif dengan memanfaatkan data sekunder dari jurnal, buku, dan laporan pemerintah untuk mengidentifikasi sifat multidimensi dari permasalahan tersebut. Temuan menunjukkan bahwa rencana repatriasi WNI dari Camp Al-Hol dan Al-Roj membutuhkan strategi komprehensif yang bersifat antisipatif. Kajian ini menekankan pentingnya foresight dan perencanaan skenario sebagai instrumen dalam memproyeksikan perkembangan situasi keamanan di masa depan, yang dipadukan dengan analisis intelijen untuk memetakan kerentanan dan langkah mitigasi. Selain itu, koordinasi efektif antar lembaga keamanan nasional, program deradikalisasi berbasis masyarakat, serta kerja sama internasional menjadi faktor penting dalam menghadapi tantangan reintegrasi. Hasil penelitian menegaskan bahwa keamanan nasional perlu dijaga melalui kebijakan adaptif yang mampu menyeimbangkan kebutuhan keamanan dengan pertimbangan kemanusiaan. Penguatan sinergi antar lembaga serta penyusunan strategi multi-skenario menjadi kunci dalam mengurangi ancaman dan memastikan bahwa kepulangan WNI yang terasosiasi Foreign Terrorist Fighters (FTF)tidak menimbulkan permasalahan baru bagi masyarakat.